1994
DOI: 10.1002/jmri.1880040106
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of disorders of the brachial plexus

Abstract: The authors evaluated 64 consecutive patients with suspected brachial plexus (BP) abnormalities of diverse cause with magnetic resonance (MR) imaging, using the body coil and a standardized protocol. Of the 43 patients for whom follow-up was available, 25 were suspected of having neoplastic involvement of the BP, nine had sustained injuries, and nine presented with BP symptoms of uncertain cause. MR imaging was 63% sensitive, 100% specific, and 77% accurate in demonstrating the abnormality in this diverse pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…Although large metastatic tumors involving the BP may be palpable, they often present in "silent" regions such as the axillary apex, the retroclavicular area, the neural foramina, the paravertebral gutter or as an infiltrative process to the adjacent fat and the perineural sheath [13]. CT and MR imaging are frequently positive in patients with palpable masses [14][15][16], but the absence of a palpable mass creates a greater diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Although large metastatic tumors involving the BP may be palpable, they often present in "silent" regions such as the axillary apex, the retroclavicular area, the neural foramina, the paravertebral gutter or as an infiltrative process to the adjacent fat and the perineural sheath [13]. CT and MR imaging are frequently positive in patients with palpable masses [14][15][16], but the absence of a palpable mass creates a greater diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Bilbey et al (23) reported that delayed radiation injury or fibrosis were usually isointense or hypointense relative to …”
Section: Discussionmentioning
confidence: 99%
“…Common causes of brachial plexopathy include trauma, neoplastic infiltration, neuralgic amyotrophy, delayed radiation injury and thoracic outlet syndrome. Bilbey et al showed that MRI is 63% sensitive and 100% specific in demonstrating the abnormality of the brachial plexus in a diverse patient population (Bilbey et al, 1994). When plexopathy is caused by a mass lesion, MRI can often determine whether the mass is intrinsic or extrinsic to the plexus.…”
Section: Plexopathymentioning
confidence: 99%